Active revegetation after mining: what is the contribution of peer-reviewed studies? - Navarro Ramos, Silvia Elisa (2022)
Knowing the state of the art on research related to post-mining active revegetation can help to improve revegetation success and identify research gaps. We performed a systematic review about active revegetation after mining and identified 203 relevant studies. Most studies were performed in the USA (34%), in regions with a temperate climate (59%) and in abandoned coal mines (45%). The studies were focused on the plantation of woody species (59%) or sowing of herbaceous species (39%). The most widely evaluated treatments were the addition of amendments (24%) and fertilizers (21%), mainly with positive and neutral effects; in general, organic amendments presented more positive effects than inorganic amendments and fertilizers. We also identified studies on the effects of plowing, inoculation of microorganisms, nurse plants, herbivore exclusion and watering. The results of these treatments should be taken with caution, because they can vary according to the functional strategies of the introduced species and the local context, such as the degree of nutrient limitation in the mining area and abiotic conditions. Further research is needed in non-temperate climates, involving long-term monitoring and with detailed descriptions of the interventions to better interpret results and general implications of active revegetation of mining areas.